p16 Expression in Non-gynaecological Squamous Cell Carcinomas and its Association with Clinicopathological Parameters - Chitturi Ramya; Uma Prasad; Krishnapriya Giduturi; Aparna Chinnam (Apollo Medicine, 2026)
Introduction: p16 is a tumour suppressor gene and is a well-established surrogate marker for human papillomavirus (HPV) DNA. It is expressed in a wide variety of squamous cell carcinomas (SCCs) in addition to cervical SCC. The sites for non-gynaecological SCC include head and neck, penis and skin. Aims and Objectives: To assess the p16 expression and its association with clinicopathological parameters in non-gynaecological SCC. Materials and Methods: A hospital-based observational study was done in a tertiary care hospital in Andhra Pradesh, India, with a sample size of 30 cases. Immunohistochemistry with p16 was done and analysed statistically. Results: The present study included resection specimens; the sites routinely encountered during the study period were oral cavity, skin and penis. Among the 30 resected specimens, 22(73.4%) were from the oral cavity (buccal mucosa, tongue, alveolus and lip), five from cutaneous sites (16.6%) and three (10%) from the penis. Overall, p16 was positive in 15 cases (50%) and negative in 15 cases (50%). There was a statistically significant association of p16 expression with lymphovascular invasion ( P = .050) and presence of lymph node metastases ( P = .023). p16 expression was correlated with age, gender, site, tumour size, depth of invasion, histologic grade, lymphovascular invasion and lymph node status at various sites such as the oral cavity, skin and penis. Significant association was not found for p16 expression with age, gender, location, histologic grade, tumour size and differentiation. Conclusion: p16 is positive in 50% of cases of non-gynaecological squamous cell carcinoma. HPV-associated tumours can be treated with radiotherapy alone.